2023
DOI: 10.1007/s11356-023-25895-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mercury and methylmercury contamination from new artisanal and small-scale gold mining along the Nile Valley, Egypt

Abstract: The past decade witnessed the initiation and boom of the Artisanal and Small-scale Gold Mining (ASGM) activities in the hyper-arid southern Egypt. The ores are mined in the Eastern Desert and then transported to the densely populated farming communities in the Nile Valley, where the river provides the water resources needed for ore processing. In search for economic benefits, the poorly educated farmers with limited technical resources transformed their cultivated lands into ASGM operations, exposing themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…This relationship between Hg concentrations in surface and groundwater is evidence of the interaction between these two environments and may be related to infiltration processes that occur when Hg present in surface water bodies is mobilized to the aquifer [ 35 ]. These findings highlight the importance of determining the sources of aquifer recharge in order to identify potential sources of contamination that may be affecting the quality of groundwater resources [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This relationship between Hg concentrations in surface and groundwater is evidence of the interaction between these two environments and may be related to infiltration processes that occur when Hg present in surface water bodies is mobilized to the aquifer [ 35 ]. These findings highlight the importance of determining the sources of aquifer recharge in order to identify potential sources of contamination that may be affecting the quality of groundwater resources [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Ahmed et al (2021) examined the dynamics of artisanal gold mining in Gashaka Local Government Area of Taraba State, noting a lack of protective gear among miners. Abdelaal et al (2023) observed clustering of artisanal and small-scale gold mining activities around the Nile waterways in Egypt, emphasizing mercury contamination sources and their impact on surrounding receptors.…”
Section: Review Of Some Empirical Studies On Miningmentioning
confidence: 95%
“…A particular critical problem associated with the artisanal gold mining is the use of mercury in the final extraction step [11,12]. Liquid mercury is used for the amalgamation process, in which there is the separation of gold by the remaining components of the ores.…”
Section: Miningmentioning
confidence: 99%
“…Moreover, there are some unsustainable and/or unregulated practices that may contribute with toxic pollutants release and/or soil degradation and, consequently, constitute stressors that may affect environmental quality. The release into environment of mercury from artisanal gold mining is a typical example of highly polluting activity [11,12]. Deforestation for illegal timber commerce [13], conversion of forest soil into crop cultures [14] and charcoal production [15], are examples of activities that degrade soil quality.…”
Section: Introductionmentioning
confidence: 99%